Bioethical models - Amo Usanos, Rafael (Acta Bioethica, 2019)
Bioethics is a mature science that allows for the use of metalanguage in order face the challenge of pluralism. In this work on metabioethics, the aims are, firstly, to compare some of the most important proposals of bioethic models. Secondly, by means of an analytical methodology two large groups of results will be presented: on the one hand, in terms of the three types of criteria used for the construction of models (anthropological, ethical and biophilosophical); and on the other hand, the presuppositions that underlie the bioethical discussions that explain pluralism and make the dialogue more difficult will be brought to light.